Ultraearly hematoma growth in active intracerebral hemorrhage. (26th July 2016) - Rodriguez-Luna, David; Coscojuela, Pilar; Rubiera, Marta; Hill, Michael D.; Dowlatshahi, Dar; Aviv, Richard I.; Silva, Yolanda; Dzialowski, Imanuel; Lum, Cheemun; Czlonkowska, Anna; Boulanger, Jean-Martin; Kase, Carlos S.; et al.
Abstract : Objective: To determine the association of ultraearly hematoma growth (uHG) with the CT angiography (CTA) spot sign, hematoma expansion, and clinical outcomes in patients with acute intracerebral hemorrhage (ICH). Methods: We analyzed data from 231 patients enrolled in the multicenter Predicting Haematoma Growth and Outcome in Intracerebral Haemorrhage Using Contrast Bolus CT study. uHG was defined as baseline ICH volume/onset-to-CT time (mL/h). The spot sign was used as marker of active hemorrhage. Outcome parameters included significant hematoma expansion (>33% or >6 mL, primary outcome), rate of hematoma expansion, early neurologic deterioration, 90-day mortality, and poor outcome. Results: uHG was higher in spot sign patients ( p < 0.001) and in patients scanned earlier ( p < 0.001). Both uHG >4.7 mL/h ( p = 0.002) and the CTA spot sign ( p = 0.030) showed effects on rate of hematoma expansion but not its interaction (2-way analysis of variance, p = 0.477). uHG >4.7 mL/h improved the sensitivity of the spot sign in the prediction of significant hematoma expansion (73.9% vs 46.4%), early neurologic deterioration (67.6% vs 35.3%), 90-day mortality (81.6% vs 44.9%), and poor outcome (72.8% vs 29.8%), respectively. uHG was independently related to significant hematoma expansion (odds ratio 1.06, 95% confidence interval 1.03–1.10) and clinical outcomes. Conclusions: uHG is a useful predictor of hematoma expansion and poor clinical outcomes in patients with acute ICH. The combination of high uHG and the spot sign is associated with a higher rate of hematoma expansion, highlighting the need for very fast treatment in ICH patients.